Type 1 equilibrative nucleoside transporter regulates astrocyte-specific glial fibrillary acidic protein expression in the striatum - Hinton, David J (BlackWell Publishing Ltd, 2014)
BACKGROUND: Adenosine signaling has been implicated in several neurological and psychiatric disorders. Previously, we found that astrocytic excitatory amino acid transporter 2 (EAAT2) and aquaporin 4 (AQP4) are downregulated in the striatum of mice lacking type 1 equilibrative nucleoside transporter (ENT1). METHODS: To further investigate the gene expression profile in the striatum, we preformed Illumina Mouse Whole Genome BeadChip microarray analysis of the caudate–putamen (CPu) and nucleus accumbens (NAc) in ENT1 null mice. Gene expression was validated by RT-PCR, Western blot, and immunofluorescence. Using transgenic mice expressing enhanced green fluorescence protein (EGFP) under the control of the glial fibrillary acidic protein (GFAP) promoter, we examined EGFP expression in an ENT1 null background. RESULTS: Glial fibrillary acidic protein was identified as a top candidate gene that was reduced in ENT1 null mice compared to wild-type littermates. Furthermore, EGFP expression was significantly reduced in GFAP-EGFP transgenic mice in an ENT1 null background in both the CPu and NAc. Finally, pharmacological inhibition or siRNA knockdown of ENT1 in cultured astrocytes also reduced GFAP mRNA levels. CONCLUSIONS: Overall, our findings demonstrate that ENT1 regulates GFAP expression and possibly astrocyte function.